De l’invisibilité du capital : La Junte des Philippines de Goya (1815) - Occhietti, Raphaelle (RACAR : Revue d'art canadienne / Canadian Art Review, 2013)
Despite its landmark status in Goya’s oeuvre, the painting The Assembly of the Royal Company of the Philippines (1815), more commonly known as The Junta of the Philippines, has attracted little scholarly attention. An austere and imposing painting, it is the depiction of a meeting of stockholders presided by a diminutive King Ferdinand VII in an interior setting that will be identified as a “finance room.” The canvas evinces a particular point of view on the relationships between the metropole and its faraway territorial possessions based on the absence of the colonies in the canvas. It will be argued that the pictorial setting of the finance room reasserts the virtual nature of the relationships between Madrid and its colonies. By comparing the Junta to contemporaneous British representations of spaces of finance, this study seeks to remove Goya’s work from the isolation in which previous accounts have largely kept it confined. This paper reveals the ways in which the mechanisms of late eighteenth and early nineteenth century finance capitalism were disclosed pictorially by one of the era’s most eminent artists.